Different Pasts for Different Political Folk: Political Orientation Predicts Collective Nostalgia Content - Stefaniak, Anna; Wohl, Michael Jeremy Adam; Sedikides, Constantine; Smeekes, Anouk; Wildschut, Tim (Frontiers in Political Science, 2021)
Collective nostalgia is a bittersweet emotion that reflects sentimental longing for valued aspects of the past of one’s group. Given that conservatism is typically associated with a general desire to preserve the societal status quo or return society to its traditional way of being, nostalgia has been theorized to be characteristic of those on the political right (i.e., conservatives). In the current work, we proposed and tested the hypothesis that collective nostalgia is experienced by both conservatives and liberals, but the content of their nostalgizing differs. Across three studies in three socio-political contexts—United States (Study 1, MTurk, N = 352), Canada (Study 2, student sample, N = 154), and England (Study 3, online panel, N = 2,345)—we found that both conservatives and liberals experienced collective nostalgia for a more homogenous and open society. However, conservatives experienced more homogeneity-focused collective nostalgia, whereas liberals experienced more openness-focused collective nostalgia. Replicating previous findings, homogeneity-focused nostalgia emerged as a positive, whereas openness-focused nostalgia emerged as a negative, predictor of intergroup attitudes. The results have both theoretical and practical significance for understanding political attitudes and behaviors. To the point, variance in the conservative and liberal political agendas is, in part, a function of a difference in their respective predisposition to nostalgize about and thus desire the return of a particular aspect of the in-group’s past.